Agricultural Growth and Rural Incomes: Rural Performance Indicators and Consumption Patterns - Arsenio M. Balisacan (Philippine Institute for Development Studies (PIDS), 1994)
This paper examines the farm-nonfarm linkages of agricultural growth and the mechanisms by which agricultural development changes the economic welfare of various groups of rural population. Parameter estimates of the Almost Ideal Demand System (AIDS) utilizing Philippine data show substantial differences in the demand responses by various population groups to changes in household incomes. In addition, construction of consistent and defined indicators of rural performance is presented.
Keywords: 330; agriculture sector; poverty; rural sector; farm lands; consumption pattern